Doctors don't Do-little: a national cross-sectional study of workplace well-being of hospital doctors in Ireland. Issue 3 (10th March 2019) - Hayes, Blánaid; Prihodova, Lucia; Walsh, Gillian; Doyle, Frank; Doherty, Sally
Abstract : Objectives: To measure levels of occupational stress, burn-out, work–life balance, presenteeism, work ability (balance between work and personal resources) and desire to practise in trainee and consultant hospital doctors in Ireland. Design: National cross-sectional study of randomised sample of hospital doctors. Participants provided sociodemographic data (age, sex), work grade (consultant, higher/basic specialist trainee), specialty, work hours and completed workplace well-being questionnaires (Effort–Reward Imbalance (ERI) Scale, overcommitment, Maslach Burnout Inventory) and single item measures of work ability, presenteeism, work–life balance and desire to practise. Setting: Irish publicly funded hospitals and residential institutions. Participants: 1749 doctors (response rate of 55%). All hospital specialties were represented except radiology. Results: 29% of respondents had insufficient work ability and there was no sex, age or grade difference. 70.6% reported strong or very strong desire to practise medicine, 22% reported good work–life balance, 82% experienced workplace stress, with effort greatly exceeding reward, exacerbated by overcommitment. Burn-out was evident in 29.7% and was significantly associated with male sex, younger age, lower years of practice, lower desire to practise, lower work ability, higher ERI ratio and greater overcommitment. Apart from the measures of work ability and overcommitment, there was no sex or age difference across any variable. However, ERI and burn-out were significantly lower in consultants than trainees. Conclusions: Hospital doctors across all grades in Ireland had insufficient work ability, low levels of work–life balance, high levels of work stress and almost one-third experienced burn-out indicating suboptimal work conditions and environment. Yet, most had high desire to practise medicine. Measurement of these indices should become a quality indicator for hospitals and research should focus on the efficacy of a range of individual and organisational interventions for burn-out and occupational stress.